The History and Development of Doctor of Health Science (DHSc) Programs in the United States - Past, Present, and Future: Part I: The Past. - Ewing, Helen; Davis, Richard; Danielsen, Randy D.; Sauers, Eric; Reesal, Robin (Internet Journal of Allied Health Sciences & Practice, 2024)
Purpose: This three-part article series will elucidate how the Doctor of Health Science (DHSc) programs in the United States were envisioned and introduced. Method: Part I discusses relevant historical information about Higher Education and the traditional Doctor of Philosophy (PhD) degree to reach this goal. It describes the transition of PhD philosophies to professional doctorates by following the historical postgraduate program paths in education, nursing, and public health. Included is a brief discussion about the rapid growth of professional doctorates. Part I ends by identifying the origins of DHSc programs within the United States system of higher education. Part II of the series reviews the evolutionary stages of professional doctorates and DHSc programs. The article compares the DHSc degree to a PhD degree and examines the current state of DHSc programs. Part III presents current and future trends among DHSc programs in the United States. It focuses on workplace expectations of doctoral graduates, changing learner demographics and needs, essential curriculum designs for students, competency-based learning, assessment for future learners, design of culminating projects critical for prospective DHSc learners, and the importance of third-generation style DHSc programs. Conclusion: These are the first papers that record the origins, development, current state, and trends of DHSc programs in the United States.